The interacting roles and relative importance of climate, topography, soil properties and mineralogical composition on soil potassium variations at a national scale in China - Li, Ting; Liang, Junjie; Chen, Xiaoqin; Wang, Huoyan; Zhang, Shirong; Pu, Yulin; Xu, Xiaoxun; Li, Hao; Xu, Jingwen; Wu, Xiaobo; Liu, Xiaojing (Catena (Giessen), 2021)
•SEM analyses explained 12.0–46% of the variations in soil K.•Climate acted as the most important factor controlling the variations in soil K.•Topographical conditions were the secondary controls of soil K variations.•Key soil properties and clay mineral showed less effect on soil K variations.•Climate, topography and clay mineral all exhibited indirect effect on soil K variations. Climatic, topographical and soil conditions are the main drivers of soil potassium (K) variations in terrestrial ecosystem. Although theoretical and empirical studies have explored the single effect of these factors on the variations of soil K, the complex interactions and relative importance of these factors is scarce worldwide and virtually absent for China agricultural ecosystem. Here, the complex interactions and the relative contributions of the environmental variables (climate, topography, key soil properties and clay mineralogical composition) to soil K variations were evaluated in China agricultural soil by using method of structural equation model (SEM). The SEM analyses explained 12.0%, 46% and 28.8% of the variations in soil exchangeable K (EK), nonexchangeable K (NEK) and total K (TK), respectively. The results also showed that climate acted as the most important factor controlling soil K variations, followed by topographical conditions, clay mineralogical composition, and key soil properties. High temperature and precipitation (climate) had directly negative effects on soil K concentrations and the negative effects were strengthened by its impacts on key soil properties and clay mineralogical composition. The effects of topography on soil K concentrations were enhanced by its effects on climate, key soil properties and soil clay mineralogical composition. Soil clay mineralogical composition affected soil K concentrations both directly and indirectly through influencing key soil properties. The unexplained variations in soil K concentrations are due to lack of data related to crop species, finer soil particles content, and the quantity and quality of K inputs. These findings advance the understanding of the patterns and mechanisms driving soil K variations, which is critical for predicting changes in soil nutrients in response to soil forming environment at the global scale.